2017
DOI: 10.1590/1981-7746-sol00098
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinaridade E Interprofissionalidade Na Estratégia Saúde Da Família

Abstract: Resumo A interdisciplinaridade e sua correlação prá-tica, a interprofissionalidade, são essenciais ao trabalho na Estratégia Saúde da Família. Objetivou-se caracterizar a perspectiva interdisciplinar na Estratégia Saúde da Família numa capital do Brasil, relacionando-a à interprofissionalidade. Realizou-se estudo transversal, exploratório e descritivo, com abordagens qualitativa e quantitativa. Os dados foram coletados no período de junho a novembro de 2014 por meio de questionários e observação participante. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
74

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(91 citation statements)
references
References 10 publications
2
15
0
74
Order By: Relevance
“…In this sense, teams that develop the collaborative practice, use it as a mechanism for effective teamwork, information exchange, interdependence, horizontal communication, confidence, help, mutual respect and responsibility among the team's professionals. [25][26] These elements emerged in the results of this study, which indicates an approximation among the findings and the scientific production.…”
Section: Discussionsupporting
confidence: 51%
“…In this sense, teams that develop the collaborative practice, use it as a mechanism for effective teamwork, information exchange, interdependence, horizontal communication, confidence, help, mutual respect and responsibility among the team's professionals. [25][26] These elements emerged in the results of this study, which indicates an approximation among the findings and the scientific production.…”
Section: Discussionsupporting
confidence: 51%
“…Notably, 62% of individuals reported having been oriented about OA at the time of their diagnosis and 56% on obesity in the UBSs and PSFs. In a study on interprofessionality in the family health strategy, Farias et al (2017) consider that interdisciplinarity has great potential to support the integral actions and is more resolutive about potential problems, especially when focused on the needs of the user. In this context, it is observed that the interdisciplinary perspective is necessary even in individualised care; moreover, the expanded conception of health, which guides integral care, implies that, in all activities, it is necessary to have knowledge integration, including individual care, so that individuals can solve their health problems (FARIAS et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In a study on interprofessionality in the family health strategy, Farias et al (2017) consider that interdisciplinarity has great potential to support the integral actions and is more resolutive about potential problems, especially when focused on the needs of the user. In this context, it is observed that the interdisciplinary perspective is necessary even in individualised care; moreover, the expanded conception of health, which guides integral care, implies that, in all activities, it is necessary to have knowledge integration, including individual care, so that individuals can solve their health problems (FARIAS et al, 2017). One way to include and list possible improvements to SUS is promotion of public policies and use data collected in population to outline guidelines and objectives to be implemented in individual and collective health, this study questions were raised that should be taken into account regarding the construction of actions assigned to professionals, encouraging interdisciplinary and correct orientation, which proved to be beneficial in issues related to the recovery of OA (DIAS et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Attentive Alerts you that the primary attention to health, considered the main mechanism of reorganization of the health care system, is preferably represented by the Family Health Strategy (FHS), which assigns the challenge of breaking with the traditional logic of health assistance for the care is based on the family and the social context. 13 We emphasize that the difficulties of professionals regarding the management of situations that involve chemical dependence have proven that the practices and actions of prevention and treatment, practically, inexistiam, due to the lack of skills for the provision of care for the users, so that the attitude of the staff is limited to referrals to specialized services.…”
Section: Methodsmentioning
confidence: 99%